2015
DOI: 10.1007/s10796-014-9542-1
|View full text |Cite
|
Sign up to set email alerts
|

A theory building study of enterprise architecture practices and benefits

Abstract: Academics and practitioners have made various claims regarding the benefits that Enterprise Architecture (EA) delivers for both individual projects and the organization as a whole. At the same time, there is a lack of explanatory theory regarding how EA delivers these benefits. Moreover, EA practices and benefits have not been extensively investigated by empirical research, with especially quantitative studies on the topic being few and far between. This paper therefore presents the statistical findings of a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 77 publications
3
65
0
4
Order By: Relevance
“…Liao et al's (2017) evidence also adds to a growing body of important work on the role of competencies and internal audit activity in organizations (Foorthuis et al 2016;Goldschmidt 2007;Huang et al 2016;Wu et al 2016). …”
Section: Editorialmentioning
confidence: 98%
“…Liao et al's (2017) evidence also adds to a growing body of important work on the role of competencies and internal audit activity in organizations (Foorthuis et al 2016;Goldschmidt 2007;Huang et al 2016;Wu et al 2016). …”
Section: Editorialmentioning
confidence: 98%
“…Various EA artifacts used in organizations as part of EA practices can be very diverse in nature. For instance, popular EA artifacts include architecture principles [3], standards [18], core diagrams [4], business capability models or maps [19], enterprise data models [20], project-start architectures [5] and many other different types of EA artifacts [1,21].…”
Section: Related Work 21 Enterprise Architecture and Its Artifactsmentioning
confidence: 99%
“…Various EA artifacts used in organizations can be very diverse in nature and range from executive-level architecture principles [3] and core diagrams [4] to rather detailed and technical project-start architectures [5]. These EA artifacts have different usage scenarios in organizations ranging from guiding IT investments [6] to ensuring compliance of separate IT projects with an organization-wide architecture [7].…”
Section: Introductionmentioning
confidence: 99%
“…Schniederjans and Yadav (2013) found that trust issues still persist between architects and business stakeholders, adversely affecting EAI outcomes. Researchers have sought to explain the "gap" in the architect and stakeholder relationship in terms of differences in the motivations and viewpoints of architects and stakeholders (Faller & De Kinderen, 2014), organizational incentives and rewards (Foorthuis et al, 2016), conflicting assumptions and expectations associated with EAI activities (Aier, 2014), and the inability of architects to coordinate EAI activities across different functional groups (Espinosa, Armour, & Boh, 2010). Sessions (2009) describes the gap between architects and their stakeholders in terms of sensemaking and argues that stakeholders may have difficulty engaging with the EAI and that architects must eliminate any barriers to stakeholder understanding: "sometimes there is an atmosphere of mystique around enterprise architecture that makes it unnecessarily complicated, resulting in lack of understanding by the people that need to understand it" (Sessions, 2009, p. 9).…”
Section: Enterprise Architecture Implementationmentioning
confidence: 99%